PENGARUH POLA ASUH NUTRISI DAN PERAWATAN KESEHATAN TERHADAP KEJADIAN STUNTING USIA 2 – 5 TAHUN DI DESA SINDANG KABUPATEN INDRAMAYU TAHUN 2019 - Nanda Yansih Putri; Meran Dewina (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2020)
Indonesia remains dealing with nutritional problem that seriously affects the quality of human resources. One of the nutritional problems, which is a primary concern today, is the high number of stunted toddlers. This research aims to determine the effect of nutrition upbringing and health care monitoring towards stunting of 2-5 year-old children in Sindang, Indramayu, 2019. This research was conducted using analytic observational methods with cross sectional approach. The sample chosen were 38 mothers who had 2-5 year-old children in 2019 (from January to December) in Sindang, Indramayu. The research sample is taken entirely from the population. The result shows that there is relationhsip between nutrition upbringing 55.3% and a good health care monitoring 60.5% conducted by mothers. In other words, the significant relationship are nutrition upbringing (p value = 0.024) and health care monitoring (p value = 0.022) of 2-5 year old children. There is a positive influence between nutrition upbringing and health care monitoring towards stunting of 2-5 year-old children in Sindang, Indramayu, 2019. Thus, mothers and health practitioners should increase their knowledge that concerns to stunting and monitor to their children.